2023
DOI: 10.1002/smll.202304720
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photothermal Activity of Nanoconjugated System via Covalent Organic Frameworks as the Springboard

Hongzhi Liang,
Shizhang Chen,
Aori Qileng
et al.

Abstract: The development of nanomaterials with high photothermal conversion efficiency has been a hot issue. In this work, a novel photothermal nanomaterial is synthesized using Prussian blue nanocubes (PBNCs) as the photothermal active substance and covalent organic framework (COF) as the substrate. The as‐prepared COF@PBNCs show a high photothermal conversion efficiency of 59.1%, significantly higher than that of pure PBNCs (32.5%). A new circuit path is generated with the combination of COF, which prevents the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…[8,9] Therefore, considerable efforts have been made to improve the photothermal conversion efficiency of PCAs or develop innovative strategies for enhancing light delivery through biological tissues to generate sufficient heat to achieve the thorough ablation of abnormal cells. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Unfortunately, the actual therapeutic temperature during the treatment is arduous to precisely monitor and control, and as a result, pursuing the highest treatment temperature is the best option to achieve the desired therapeutic efficiency, which probably carries a risk of thermal damage to the surrounding tissue. It is reported that the highest temperature of the skin surface near the lesion tissue could reach temperatures as high as 60 °C or even 70 °C during PTT, which is bound to cause empyrosis to the skin tissue, as well as other surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Therefore, considerable efforts have been made to improve the photothermal conversion efficiency of PCAs or develop innovative strategies for enhancing light delivery through biological tissues to generate sufficient heat to achieve the thorough ablation of abnormal cells. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Unfortunately, the actual therapeutic temperature during the treatment is arduous to precisely monitor and control, and as a result, pursuing the highest treatment temperature is the best option to achieve the desired therapeutic efficiency, which probably carries a risk of thermal damage to the surrounding tissue. It is reported that the highest temperature of the skin surface near the lesion tissue could reach temperatures as high as 60 °C or even 70 °C during PTT, which is bound to cause empyrosis to the skin tissue, as well as other surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%
“…From the connected sensing system, quantitative information on the analyte concentration or activity responsible for the voltage signal is then revealed. PB has been widely used in the detection of pollutants, ions, and mycotoxins. PB films are not without challenges, including a limited stability, the need for a contacting electrolyte solution, a prolonged response time, and a narrow response range of about 100 mV that limits the dynamic range of the resulting sensor …”
mentioning
confidence: 99%